Kearifan Lokal Masyarakat Kampung Walian II : Suatu Studi Atas Hubungan Manusia dan Alam di Tengah Tantangan Ekologis Masa Kini - Rumende, Fransisco; Kussoy, Jordan Alexander; Toreh, Celine; Limarloy, Mathias; Aprilian, Canelio; Mamuaya, Joshua (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2025)
This study aims to explore the ecological views and practices of the community in Walian II Village amid the global ecological crisis. Based on in-depth interviews with local leaders, it was found that nature is understood not only as a physical resource but also as an integral part of spiritual and cultural life. Local traditions such as giving thanks for the harvest, prohibitions against indiscriminate tree-cutting, and replanting reflect a harmonious relationship between humans and nature. This worldview is reinforced by Catholic teachings, particularly through the ecological appeals in the Laudato Si’ encyclical. However, these values are increasingly being eroded by the forces of modernization, individualism, and consumerist lifestyles. Despite this, local initiatives such as reforestation, the use of organic fertilizers, and faith-based environmental education demonstrate ongoing efforts toward sustainable conservation. This study underscores the importance of preserving local values as a contextually meaningful ecological solution that is spiritual, ethical, and cultural in nature. It recommends cross-sector collaboration in building collective ecological awareness rooted in tradition, faith, and scientific knowledge.